1981
DOI: 10.1017/s0305000900003433
|View full text |Cite
|
Sign up to set email alerts
|

Content and context in early lexical development

Abstract: Investigators have targeted the onset of reference in children at varying points on the developmental continuum. Their viewpoints seem to be related to issues of the contextual flexibility, content and composition of the lexicon in comprehension and production. This study considered all of the variables in the early vocabularies of 32 children with a mean age of 1; 1·7. An intensive maternal interview was used to obtain data on the words comprehended and produced by the children and the contexts which supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 7 publications
6
87
1
3
Order By: Relevance
“…This is actually somewhat higher than the coefficients reported in some of our other studies (e.g. Snyder et al, 1981). Nevertheless, we can see from Figure C1 that a significant number of children are producing very little meaningful speech despite receptive vocabularies of 150 words or more.…”
Section: Event-related Brain Potentials (Erp)contrasting
confidence: 58%
See 1 more Smart Citation
“…This is actually somewhat higher than the coefficients reported in some of our other studies (e.g. Snyder et al, 1981). Nevertheless, we can see from Figure C1 that a significant number of children are producing very little meaningful speech despite receptive vocabularies of 150 words or more.…”
Section: Event-related Brain Potentials (Erp)contrasting
confidence: 58%
“…For many years, parents and psycholinguists have known about children who appear to understand far more than they are able or willing to say (Goldin-Meadow, Seligman & Gelman, 1976;Benedict, 1979;Snyder, Bates & Bretherton, 1981;Bates et al, 1988). The prevalence of this pattern in normal children has now been established on a large scale in the MacArthur CDI norming study (Fenson et al, in press; see also Thal, Fenson and Bates, in preparation).…”
Section: Event-related Brain Potentials (Erp)mentioning
confidence: 99%
“…Subsequent studies based on larger samples and more reliable measures have confirmed these early estimates, showing that comprehension is first evident around 8 months with word production beginning around the first birthday (Bloom, 1973;Snyder, Bates, & Bretherton, 1981). Research methods have changed considerably, but children evidently have not.…”
Section: Developmentmentioning
confidence: 93%
“…In the diary studies that provided the first systematic observations of early language development, Tiedemann (1787Tiedemann ( /1927 (Bloom, 1973;Snyder, Bates, & Bretherton, 1981). Research methods have changed considerably, but children evidently have not.…”
Section: Developmentmentioning
confidence: 99%
“…Our first insights into this tight correlation came in a longitudinal study of 27 children who were observed at 10, 13, 20 and 28 months of age, using a combination of structured observations (at home and in the laboratory) and parental report ; see also Bretherton, McNew, Snyder, & Bates, 1983;Snyder, Bates, & Bretherton, 1981). Among other things, we examined the concurrent and predictive relation between vocabulary size and grammatical status at 20 and 28 months of age.…”
Section: Grammar and The Lexicon In Normally Developing Childrenmentioning
confidence: 99%